Hubungan Pengetahuan dan Dukungan Suami dengan Kepatuhan Ibu Hamil Mengkonsumsi Tablet Fe - Desi Gultom; Khairunnisa Situmorang; Friza Novita Sari Situmorang; Humaida Hanum; Nela Sari (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
The function of Fe tablets is to act as one of the components in forming myoglobin (a protein that carries oxygen to muscles), collagen (a protein found in bones). In pregnant women, iron plays an important role in fetal growth. This study aims to determine the relationship between husband's knowledge and support and compliance with pregnant women consuming Fe tablets at the Kampung Mesjid Community Health Center, Kec. Kualuh Hilir in 2023. This type of research is an analytical survey with a cross-sectional research design. The population is all pregnant women at the Kampung Mesjid Community Health Center, Kec. Kualuh Hilir in 2023 as many as 40 people. The number of samples used was 40 people obtained using total sampling techniques. The data analysis technique uses chi square. The results obtained in this study were that 24 respondents (84.4%) had good knowledge of compliantly consuming Fe tablets and 24 respondents (60%) had good husband support for compliantly consuming Fe tablets among pregnant women. Based on the chi square test results, there is a relationship between knowledge and compliance with pregnant women consuming Fe tablets with a P value = 0.002 < 0.05, there is a relationship between husband's support and compliance with pregnant women consuming Fe tablets with a P value = 0.008 < 0.05. The conclusion is that there is a relationship between husband's knowledge and support and pregnant women's compliance with consuming Fe tablets. It is recommended that pregnant women increase their compliance in consuming Fe tablets during their pregnancy to maintain the health of themselves and their womb.